"Nadine" de Louise Michel et de Jean Winter : une approche anarchiste du théâtre de contestation sociale, ou comment contourner la censure - Kaczmarek, Tomasz (2023)
This study focuses on the play “Nadine” (directed in 1882), which is a free adaptation of the novel Le “Bâtard imperial” [The Imperial Bastard] written by Louise Michel in collaboration with Jean Winter. The dramatic text fits perfectly into the aesthetics of the theater of social protest, which, at the turn of the 20th century, enjoyed an undeniable reputation with the popular public, above all thanks to its subversive message. The analysis of the drama, which repeatedly alludes to the days of the Paris Commune (1871), reveals certain strategies implemented by the author in order to thwart the vigilance of power. First of all, Michel places the action of the play in Poland during the Cracow Uprising in 1846. Evoking an episode in a remote country that remained subject to the three great powers should not, therefore, immediately arouse the suspicions of the police. The former communard seems to be using this revolt of the Poles as a pretext to revive the grand gestures of the Parisian people. It is for the same reasons that Michel writes this play in accordance with melodramatic aesthetic because the focus on the emotional conflict in the background of the revolution was supposed to dispel mistrust authorities.
Keywords: "Nadine"; French Theater of Social Protest; anarchism; the Paris Commune; the Cracow Uprising